Clinical and endoscopic features of the upper digestive tract pathology in children and adolescents depending on age - L.K. Parkhomenko; L.A. Strashok; E.M. Zavelya; M.Yu. Isakova; A.V. Yeshchenko; Zh.V. Polishchuk (Zaslavsky O.Yu., 2017)
Background. The purpose was to determine the structure and age characteristics of clinical and endoscopic features of gastroduodenal pathology in adolescence. Materials and methods. The study included 493 adolescents between 10 and 14 years of age and 444 adolescents aged 15 to 18 years. Clinical, laboratory and instrumental studies were conducted (esophagogastroduodenoscopy, intragastric pH-metry, Helicobacter pylori DNA). Results. The study showed that in adolescence, the inflammatory lesions of the upper digestive tract predominate in both age groups. Destructive lesions occur in 8-10 % of patients in the 10-14 age group, and their incidence increases 2 times in boys and 1.5 times - in girls in the 15-18 age group. Motility disorders of the upper digestive tract are determined in 30 % of patients regardless of age, more often in girls. Lesions of the upper digestive tract are usually accompanied by basal gastric hyperacidity in boys, while in girls the basal normacidity is more often determined. Helicobacter pylori infection is detected in 2/3 of adolescents with disorders of the upper digestive tract, slightly more often in the 10-14 age group. Conclusions. The results obtained in the course of the study can focus the directions of etiotropic and pathogenetic therapy for the upper digestive tract diseases depending on the age and gender of the patients.